Low-complexity and low-latency implementation of the Godard - Endres, T.J.
This paper discusses methods for calculating and implementing the update error term for the popular blind equalization algorithm known as Godard's (1980) algorithm, or the constant modulus algorithm (CMA), without the use of multipliers so that chip area and signal latency are both substantially reduced. One approach uses a decision-directed CMA update term, and another uses region-based quantization. The quantized error term can be calculated using a look-up table in place of costly multipliers and adders. Baseband and passband implementations are discussed, and computer simulations verify our methods
Keywords: Godard's algorithm; Godard/CMA update; Adaptive equalizer; Baseband implementation; Blind equalization algorithm; Computer simulations; Constant modulus algorithm; Decision-directed CMA update term; Look-up table; Low-complexity implementation; Low-latency implementation; Passband implementation; Quantized error term; Region-based quantization; Update error term